An update on type 1 diabetes treatments: insulin treatment, cell therapy and transplantation - Hani, Homayoun; Mohd Lila, Mohd Azmi; Abdullah, Rasedee; Allaudin, Zeenathul Nazariah; Sarsaifi, Kazhal; Abdullah, Faez Firdaus Jesse (Universiti Putra Malaysia Press, 2018)
Diabetes is one of the major life-threatening health problems worldwide today. It is one of the most fast-growing diseases that cause many health complications and a leading cause of decreasing life expectancy and high mortality rate. Many studies have suggested several different types of intervention to treat Type 1 diabetes such as insulin therapy, islet transplantation, islet xenotransplantation and stem cell therapy. However, issues regarding the efficacy, cost and safety of these treatments are not always well addressed. For decades, diabetes treatments with few side effects and long-lasting insulin independence has remained one of the most challenging tasks facing scientists. Among the treatments mentioned above, application of human islet transplantation in patients with type 1 diabetes has progressed rapidly with significant achievement. Again, the lack of appropriate donors for islet transplantation and its high cost have led researchers to look for other alternatives. In this review, we discuss very pertinent issues that are related to diabetes treatments, their availability, advantages, disadvantages and also cost.